POTENTIAL OF SEA LEVEL RISE IMPACT ON SOUTH CHINA SEA: A PRELIMINARY STUDY IN TERENGGANU, MALAYSIA - Muhammad Barzani, Gasim; Mohd Khairul Amri, Kamarudin; Hafizan, Juahir (2018)
The effect of the sea level rise was involved the existence of sea water intrusion and coastal erosion phenomenon in the coastal of Terengganu. This study aim to determine fluctuation of high and low tides of the South China Sea in their relation to water quality value of Marang and Paka Rivers as well as from wells monitoring along the Terengganu Coast. Sampling was carried out twice during high and low tides, first in November 2012 and was repeated in November 2015. For the river quality study, it involves six parameters and involves nine parameters for well survey. Two-way t-test was used under statistical analysis to differentiate between two samplings. The result of the study can be assured that sea level rise resulting in decreased concentration of salinity, EC and TDS from upstream to downstream as a result of qualitatively rise of sea level at Terengganu beach as an impact of global warming events.